2015
DOI: 10.1021/acs.biomac.5b01379
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Poly(ε-caprolactone)/α-Cyclodextrin Pseudorotaxane Nanofibers

Abstract: Multifunctional scaffolds comprising neat poly(ε-caprolactone) (PCL) and α-cyclodextrin pseudorotaxanated in α-cyclodextrin form have been fabricated using a conventional electrospinning process. Thorough in-depth characterizations were performed on the pseudorotaxane nanofibers prepared from chloroform (CFM) and CFM/dimethylformamide (DMF) utilizing scanning electron microscopy (SEM), transmission electron microscopy (TEM), rheology, differential scanning calorimetry (DSC), thermogravimetric analyses (TGA), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 41 publications
5
44
0
1
Order By: Relevance
“…Electrospun fibers typically have diameters in the nano-submicron size range and offer a high surface area to volume ratio (Fig.3iii) [168]. In addition, due to their small fiber diameters, they mimic the nano-sized physical characteristics of the ECMs.…”
Section: Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospun fibers typically have diameters in the nano-submicron size range and offer a high surface area to volume ratio (Fig.3iii) [168]. In addition, due to their small fiber diameters, they mimic the nano-sized physical characteristics of the ECMs.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Image (i) reprinted with permission from [137], copyright Elsevier 2006. Image (ii) reproduced with permission from ref [168], copyright American Chemical Society 2015. Images (iii) reproduced with permission from ref [172].…”
Section: Figurementioning
confidence: 99%
“…Furthermore, PCL has poor cellular adhesion properties on its own, without some form of functionalization [47]. Numerous approaches to improve its bioactivity, including copolymerization, surface functionalization, and blend formations have been used to overcome this disadvantage [48,49]. For instance, Chang et al demonstrated that poly(epsilon-caprolactone)-graft-type II collagen-graft-chondroitin sulfate (PCL-g-COL-g-CS) scaffolds fabricated via particulate leaching and surface modification of PCL can be loaded with type II collagen and chondroitin sulfate to allow for proliferation of chondrocytes in vitro [50].…”
Section: Synthetic and Natural Biomaterials For Tissue Engineeringmentioning
confidence: 99%
“…PCL is a biocompatible and biodegradable polymer making it a good candidate for medical applications (Narayanan, Aguda, et al, ; Safaeijavan, Soleimani, Divsalar, Eidi, & Ardeshirylajimi, ). In two separate studies that conducted by our group, we demonstrated that PCL and pulsed electromagnetic field have a synergistic effect on osteogenic differentiation potential of MSCs and human induced pluripotent stem cells (iPSCs) (Ardeshirylajimi & Khojasteh, ; Arjmand, Ardeshirylajimi, Maghsoudi, & Azadian, ).…”
Section: Nanofibrous Fabrication Methodsmentioning
confidence: 99%